Cien años de guerras mixes: territorialidades prehispánicas, expansión burocrática y zapotequización en el Istmo de Tehuantepec durante el siglo XVI - Barros van Hövell tot Westerflier, Alonso (El Colegio de México, A.C., 2007)
Scattered colonial records referring to the area of Jaltepec, in the isthmus of Tehuantepec, reveal how Zapotecs and Spaniards gradually created during the sixteenth century a bureaucratic network which eventually led the former to succeed in their age-old war against the Mixes. Whereas the Zapotecs were already considered efficient and bureaucratic litigants by the first decade after Cortes' arrival, the insubordinate Mixes continued fighting  during  the whole century. The resulting documentary lag has led to the belief that the “Mixes of Oaxaca” lacked the more civilized Prehispanic history of those Mixes who quickly adopted  Spanish literacy, as did their Zapotec enemies. However, a more geographicallyin formed reading of this ethnohistorical puzzle  suggests that the presence and territorial coherence of the Mixes-Zoques-Popolucas of Oaxaca, Chiapas, Tabasco, and Veracruz were greater that we suppose, and that Zapotec influence in the Isthmus of Tehuantepec was a milestone in the Spanish colonization of America.